2018
DOI: 10.1097/ccm.0000000000003157
|View full text |Cite
|
Sign up to set email alerts
|

Near-Continuous Glucose Monitoring Makes Glycemic Control Safer in ICU Patients*

Abstract: Use of a continuous glucose monitoring-based strategy decreased the incidence and severity of hypoglycemia, thus improving the safety of glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 36 publications
0
38
0
1
Order By: Relevance
“…To our knowledge, this study represents the first time a CE-marked CGM that was designed for use in the ICU setting has been integrated with glucose control software designed for use in the ICU setting to create a fully autonomous glucose control system. An advantage the EIRUS CGM has over other CE-marked CGM systems [31,32] is that its microdialysis sensing method does not require aspiration of blood across an ex-vivo glucose sensor. Systems that require aspiration of blood will be more prone to failure from inability to aspirate blood from the catheter due to biofilm, thrombus, or position of the catheter against the venous/arterial wall [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study represents the first time a CE-marked CGM that was designed for use in the ICU setting has been integrated with glucose control software designed for use in the ICU setting to create a fully autonomous glucose control system. An advantage the EIRUS CGM has over other CE-marked CGM systems [31,32] is that its microdialysis sensing method does not require aspiration of blood across an ex-vivo glucose sensor. Systems that require aspiration of blood will be more prone to failure from inability to aspirate blood from the catheter due to biofilm, thrombus, or position of the catheter against the venous/arterial wall [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…They found that tight control did not reduce the risk of short-term mortality, but lead to severe hypoglycemia (<2.2 mmol/l) more frequently [12]. Preiser J C et al recommended that a continuous glucose monitoring-based strategy may decrease the incidence and severity of hypoglycemia, every 5-15 min may be the best time interval [13]. Many clinical guidelines recommend target blood glucose between 140 and 180 mg/dL (7.8 and 10 mmol/L) for most patients in the intensive care unit (ICU) [14].…”
Section: Discussionmentioning
confidence: 99%
“…30 Finally, at the time of this study, our institution was not using newer technologies, such as intravascular continuous BG monitoring, and thus we are unable to draw conclusions regarding the impact of vitamin C on this technology. 32 A potential for interference with vitamin C exists because most glucose sensors use the glucose oxidase-based method, but further studies are needed to evaluate the effects using this technology. 33…”
Section: Discussionmentioning
confidence: 99%